Minimal-Contact Versus Standard Cognitive Behavioral Therapy for Irritable Bowel Syndrome: Cost-Effectiveness Results of a Multisite Trial - Dunlap, Laura J; Jaccard, James; Lackner, Jeffrey M (Annals of behavioral medicine, 2021)
Irritable bowel syndrome (IBS) is a common, often disabling gastrointestinal (GI) disorder for which there is no satisfactory medical treatment but is responsive to cognitive behavior therapy (CBT). To evaluate the costs and cost-effectiveness of a minimal contact version of CBT (MC-CBT) condition for N = 145 for IBS relative to a standard, clinic-based CBT (S-CBT; N = 146) and a nonspecific comparator emphasizing education/support (EDU; N = 145). We estimated the per-patient cost of each treatment condition using an activity-based costing approach that allowed us to identify and estimate costs for specific components of each intervention as well as the overall total costs. Using simple means analysis and multiple regression models, we estimated the incremental effectiveness of MC-CBT relative to S-CBT and EDU. We then evaluated the cost-effectiveness of MC-CBT relative to these alternatives for selected outcomes at immediate posttreatment and 6 months posttreatment, using both an intent-to-treatment and per-protocol methodology. Key outcomes included scores on the Clinical Global Impressions-Improvement Scale and the percentage of patients who positively responded to treatment. The average per-patient cost of delivering MC-CBT was $348, which was significantly less than the cost of S-CBT ($644) and EDU ($457) (p < .01). Furthermore, MC-CBT produced better average patient outcomes at immediate and 6 months posttreatment relative to S-CBT and EDU (p < .01). The current findings indicated that MC-CBT is a cost-effective option relative to S-CBT and EDU. As predicted, MC-CBT was delivered at a lower cost per patient than S-CBT and performed better over time on the primary outcome of global IBS symptom improvement.